Treatment Stratification in First-Line Recurrent or Metastatic Head and Neck Cancer, on Behalf of the EORTC Young Investigator Head and Neck Cancer Group - Klinghammer, Konrad; Lorini, Luigi; Nevens, Daan; Simon, Christian; Machiels, Jean-Pascal; Bossi, Paolo (Frontiers in Oncology, 2022)
Multiple factors differentially influence treatment decisions in the first line treatment of recurrent/metastatic HNSCC. The EORTC Young investigator group launched a survey among treating physicians to explore the main influencing factors for treatment stratification. The questionnaire was posted as a web-survey link from May to August 2020. Next to defining the factors that mostly influence therapeutic decision the survey was complemented by a clinical case discussion of five patient cases. A total of 118 responses from 19 countries were collected. The key factors identified to guide treatment decision were performance status, PD-L1 Expression, time from last systemic treatment above or below 6 months, and disease burden. Prospective evaluation of patient characteristics and additional potential predictive biomarkers for novel treatment options remains an important question to stratify personalized treatment for RM HNSCC.